2021
DOI: 10.3390/w13141965
|View full text |Cite
|
Sign up to set email alerts
|

Karst Recharge Areas Identified by Combined Application of Isotopes and Hydrogeological Budget

Abstract: The identification of recharge areas in karst aquifers allows us to perform sustainable management of these groundwater resources. Stable isotopes (δ18O and δ2H) have been largely used to provide information about recharge elevation in many mountainous regions. In this paper, an improved version of a recent “isotope-driven model”, for the identification of recharge areas, was applied to Capodacqua di Spigno Spring (south of the Latium region). The model upgrade consists of a preliminary check procedure to esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In fact, many of the main springs may have been fed by not only rainfall but also by snow melt coming from the Campo Imperatore plain (Lorenzi et al 2022;Scozzafava and Tallini 2001;Amoruso et al 2014), with an estimation of about 75% of precipitation feeding the aquifer by infiltration. In this scenario, stable water isotopes are useful to understand and delineate the catchment area of the main springs (Barbieri et al 2005;Sappa et al 2018;Rusjan et al 2019;Iacurto et al 2021). Monitoring changes in stable isotopes over time and space can provide a better understanding of aquifer recharge and spring discharge links, which are critical to the study of groundwater hydrodynamics (Barbieri et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many of the main springs may have been fed by not only rainfall but also by snow melt coming from the Campo Imperatore plain (Lorenzi et al 2022;Scozzafava and Tallini 2001;Amoruso et al 2014), with an estimation of about 75% of precipitation feeding the aquifer by infiltration. In this scenario, stable water isotopes are useful to understand and delineate the catchment area of the main springs (Barbieri et al 2005;Sappa et al 2018;Rusjan et al 2019;Iacurto et al 2021). Monitoring changes in stable isotopes over time and space can provide a better understanding of aquifer recharge and spring discharge links, which are critical to the study of groundwater hydrodynamics (Barbieri et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of these data typically requires a multidisciplinary study approach that includes using more specialized investigation methods to estimate the recharge or contributing areas of karst springs (Ginsberg & Palmer, 2002). Recent research also showed that if hydrogeological context in karst area wants to be fully understood, it is necessary to control hydrological factors which affect its water budget (Gil-Márquez et al, 2021), while the identification of recharge areas of karst aquifers can enable sustainable management of groundwater resources (Iacurto et al, 2021). It was shown that inclusion of different tracers in monitoring can greatly reduce ambiguity of interpretation, but also that complete certainty in hydrogeology research of karst aquifers is still very hard to achieve (Stroj et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Infact, many of the main springs may have been fed by not only rainfall, but also by snow melting coming from the Campo Imperatore plain (Lorenzi et al, 2022;Scozzafava and Tallini, 2001;Amoruso et al, 2014), with an estimation of about 75% of precipitation feeding the aquifer by in ltration. In this scenario, stable water isotopes are useful to understand and delineate the catchment area of the main springs (Barbieri et al, 2005;Sappa et al, 2018;Rusjan et al, 2019;Iacurto et al, 2021). Monitoring changes in stable isotopes over time and space can provide a better understanding of aquifer recharge and spring discharge links, which are critical to the study of groundwater hydrodynamics (Barbieri et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The stable isotopes such as δ 2 H and δ 18 O, acting as conservative tracers (Calligaris et al, 2018;Iacurto et al, 2021), play a key role in the karstic aquifer. In fact, the isotopic concentration of the rainwater impacting the soil is strictly linked to the falling altitude (Giustini et al, 2016).…”
Section: Introductionmentioning
confidence: 99%